Understanding terra preta: broader environmental implications of anthrosol use - Hendrickson, Halle (My University, 2015)
Recent archaeological discoveries in the Amazon region are altering common perceptions on pre-Columbian indigenous populations as well as our understanding of Amazonian ecology. The presence of terra preta soil scattered throughout the Amazon Basin carries major implications – both for pre-Columbian indigenous populations of the region and for modern-day agricultural practices in the tropics. In a rapidly changing physical world, with the effects of deforestation and increasing atmospheric CO2 levels, the potential of anthropogenic soils and biochar are incredibly valuable.
Presented on December 3, 2015 at the environmental archaeology student poster session (ANTH 411) at MacEwan University Library in Edmonton, Alberta.
Keywords: terra preta; biochar technology; carbon sequestrian